Effects of autophagy inhibition by chloroquine on hepatic stellate cell activation in CCl4‐induced acute liver injury mouse model. Issue 1 (9th November 2021) - Le, Trinh Van; Dinh, Ngoc Bao Thi; Dang, Minh Thanh; Phan, Nhan Chinh Lu; Dang, Loan Tung Thi; Grassi, Gabriele; Holterman, Ai Xuan Le; Le, Huy Minh; Truong, Nhung Hai
Abstract: Background and Aim: Hepatic stellate cells (HSCs) activation, a critical event in liver fibrosis, has been recently shown to be related to autophagy. Determine whether chloroquine (CQ) could affect (i) the activation of HSC in vivo and (ii) the hepatic damage in a mice acute liver injury model. Methods: The acute liver injury was induced in BALB/c mice by carbon tetrachloride (CCl4 group); 24 h before and after CCl4 administration animals were treated by CQ (CCl4 + CQ group). As control, mice treated by olive oil were considered. After 48 h from CCl4 /olive oil administration, blood samples, liver tissues, and HSCs were harvested for analysis. Results: In vivo, CQ attenuates CCl4 ‐induced acute liver damage as evidenced by (i) the reduction of liver enlargement, (ii) the reduction of liver swelling and necrosis also supported by a certain decrease of circulating transaminases level, and (iii) the reduction of liver fibrosis evaluated by collagen deposition and α‐sma protein expression. In HSCs isolated from CQ treated group, we observed the inhibition of autophagy proved by the increase in p62 protein and the decrease of lc3 protein. In addition, CQ reduced the expression of the HSCs activation markers α‐sma/collagen‐I and down‐regulated the expression of the proliferative marker ki67. Conclusion: The autophagy attenuation exerted by CQ together with the reduction of the expression of the proliferation marker in HSCs can lessen the acute liver damage potentially opening the way to novel therapeutic approaches for hepatic fibrosis.